2011
DOI: 10.1074/jbc.c110.210211
|View full text |Cite
|
Sign up to set email alerts
|

The GAS41-PP2Cβ Complex Dephosphorylates p53 at Serine 366 and Regulates Its Stability

Abstract: The p53 tumor suppressor is principally regulated by posttranslational modifications and proteasome-dependent degradation. Various kinases have been shown to phosphorylate p53, but little is known about the counteracting phosphatases. We demonstrate here that the newly identified complex GAS41-PP2C␤, and not PP2C␤ alone, is specifically required for dephosphorylation of serine 366 on p53. Ectopic expression of GAS41 and PP2C␤ reduces UV radiation-induced p53 up-regulation, thereby increasing the cell survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Part of its tumor-promoting activity is thought to be mediated through negative regulation of the p53 pathway. For example, GAS41 physically interacts with p53 and regulates p53 protein stability independently of the SRCAP or Tip60/ p400 complex (Park et al 2011). In addition, GAS41 is present at the promoters of p53-regulated genes, such as p21, and suppresses gene expression (Park and Roeder 2006;Pikor et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Part of its tumor-promoting activity is thought to be mediated through negative regulation of the p53 pathway. For example, GAS41 physically interacts with p53 and regulates p53 protein stability independently of the SRCAP or Tip60/ p400 complex (Park et al 2011). In addition, GAS41 is present at the promoters of p53-regulated genes, such as p21, and suppresses gene expression (Park and Roeder 2006;Pikor et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Also knockdown of PPM1B in wild-type ES cells did not affect proliferation suggesting that PPM1B expression is specifically required during the early stages of embryogenesis and does not affect cell-cycle progression [34]. So far, only a limited number of substrates for PPM1B have been identified, including the kinases IKKβ [IκB (inhibitor of nuclear factor κB) kinase] [35] and TAK1 (transforming growth factor-β-activated kinase 1) [36], the proapoptotic protein Bad [37], the cyclin-dependent kinases CDK2 and CDK6 [38], the transcription factor p53 [39] and the CDK9 subunit of P-TEFb (positive transcription elongation factor b) [40]. Interestingly, Iankova et al [9] showed that CDK9mediated phosphorylation of PPARγ on Ser 112 results in enhanced transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GAS41 is required for dephosphorylation of serine 366 on TP53 that forms a complex with PP2CB. The cell survival upon genotoxic DNA damage was increased after ectopic expression of GAS41 and PP2CB by reducing the TP53 upregulation (Park et al, 2011). NuMA appears to be a key to further understanding the role of GAS41 in mitosis.…”
Section: Discussionmentioning
confidence: 99%